2015
DOI: 10.12974/2309-6136.2015.03.01.1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evaluation of Retinal and Choroidal Structure in a Mouse Model of Long-Lasting Diabetes. Effect of Topical Treatment with Citicoline

Abstract: Recent evidences indicate early, diabetes-driven, retinal neurodegeneration as the origin of diabetic retinopathy. To verify the possibility to prevent the disease, we investigated in a mouse model of type 1 diabetes the effect of long-lasting hyperglycemia on retinal and choroidal structures and, in parallel, we tested the effect of topical treatment with the neuroprotective agent citicoline. Forty wild-type C57B6 mice were included in this study. Diabetes was induced by a single intravenous injection of allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Recently, the neuroprotective effect of citicoline has been demonstrated on retinal nerve fibers in hyperglycemia conditions. In a mouse model of diabetes it has been shown that citicoline eye drops counteracts retinal nerve fibers layer thinning [ 67 ]. Results are in agreement with those of a previous study investigating the effect of BDNF, neurotrophin-4 (NT-4), and citicoline on neuronal apoptosis and neurite regeneration in cultured rat retinas exposed to high glucose.…”
Section: Role Of Citicoline In Glaucoma: Current Evidencementioning
confidence: 99%
“…Recently, the neuroprotective effect of citicoline has been demonstrated on retinal nerve fibers in hyperglycemia conditions. In a mouse model of diabetes it has been shown that citicoline eye drops counteracts retinal nerve fibers layer thinning [ 67 ]. Results are in agreement with those of a previous study investigating the effect of BDNF, neurotrophin-4 (NT-4), and citicoline on neuronal apoptosis and neurite regeneration in cultured rat retinas exposed to high glucose.…”
Section: Role Of Citicoline In Glaucoma: Current Evidencementioning
confidence: 99%
“…After eight months of induced diabetes, there was a reduction in thickness of both the choroid and the retinal layers, including the retinal nerve fiber layer, ganglion cell complex, and the ganglion cells/inner plexiform layer, in diabetic versus control mice. However, there was no significant thinning in the corresponding retinal layers in citicoline-treated diabetic mice [77], suggesting a neuroprotective action.…”
Section: Experimental Evidencementioning
confidence: 82%
“…The neuroprotective effect of citicoline against the toxic effects of prolonged hyperglycemia on the retina was examined by Zerbini et al in a mouse model of type 1 diabetes [77]. After eight months of induced diabetes, there was a reduction in thickness of both the choroid and the retinal layers, including the retinal nerve fiber layer, ganglion cell complex, and the ganglion cells/inner plexiform layer, in diabetic versus control mice.…”
Section: Experimental Evidencementioning
confidence: 99%
“…The neuroprotective effect of Citicoline on retinal nerve fibers in hyperglycemia conditions has also been proven by using Citicoline eye drops in a mouse model of diabetes [20].…”
Section: Experimental Studiesmentioning
confidence: 98%